Perfluoroalkylation Reactions by Electron Donor‐Acceptor Complexes: Recent Advances - Yerien, Damián Emilio (2024)
This Perspective analyses the perfluoroalkylation reactions by electron donor-acceptor (EDA) complexes since 2018, while summarizes, in Tables 1-3, the vast majority of representative perfluoroalkylation reactions of various classes of organic compounds by EDA complexes and halogen-bonding interactions. Numerous intriguing reaction methodologies and valuable synthetic instances have emerged. We aim to delve into these new examples comprehensively, while also contemplating the future directions in the field. Subsequent sections will elaborate on the perfluoroalkylation of (hetero)aromatic compounds, carbon-carbon multiple bonds, perfluoroalkylation of carbonyl compounds, and perfluoroalkylation of isocyanides, covering their synthetic scope and mechanistic insights.